TEACHER PERSPECTIVES ON COHERENCE AND CONTINUITY IN ENGLISH TEXTBOOKS (Journal of Universal Science Research, 2025)
This article examines the critical elements of coherence and continuity in English language teaching textbooks, highlighting teacher perspectives on their importance for effective learning. It underscores how structured content and consistent pedagogical approaches can enhance student engagement and understanding.